Problematika Evaluasi Pembelajaran Bahasa Arab di Masa Pandemi Covid-19 - Arsyad Itsarul Ikhwan; Syihabuddin; Ali, Mad (Al-Ma‘rifah, 2021)
This study aims to determine the problem of evaluating Arabic learning. This research used a qualitative descriptive and subjects were Arabic language teachers and grade IX students at SMPIT Insan Rabbani, Bekasi Barat. The data collection technique used observation, interview, and documentation techniques, while the data validation technique used triangulation techniques, namely triangulation of data sources and methods. data analysis. The results showed that: (1) the planning of the evaluation of Arabic learning at SMPIT Insan Rabbani is quite good; (2) the implementation of the evaluation of Arabic learning is carried out using the google form media; (3) the problem is that it is difficult to know the students’ Arabic skills and the character or behavior of the students are difficult to monitor. The location of the house is not covered by the internet network, including minimalist student internet quotas, or an unstable internet network. Efforts made by teachers in dealing with these problems by temporarily asking students to move locations that are accessible to the internet network.